Analysis of the Content of the PAI Curriculum in Schools - Nazid Zaki Fuadi; Muhammad Zuhdi; Bobi Erno Rusadi (Al-Alim: Jurnal Pendidikan Agama Islam, 2026)
The Islamic Religious Education (PAI) curriculum plays a strategic role in shaping the character, morals, and personality of students who are faithful and devout. This article aims to analyze the content of the PAI curriculum in schools to determine its alignment with the goals of Islamic education and the demands of modern times. The analysis covers curriculum development principles, foundational elements of preparation, and the transformation of the PAI curriculum in Indonesia across different eras. The results show that the PAI curriculum has undergone significant development, from a simple post-independence curriculum to the "Kurikulum Merdeka," which emphasizes the formation of the Pancasila Student Profile and religious moderation. The conclusion of this study reinforces that an ideal PAI curriculum must be adaptive, contextual, and able to balance cognitive, affective, and psychomotor aspects to address global challenges.